The impact of the collapse of communism and EU accession on language education policy and practice in Central and Eastern Europe: two case-studies focussing on English and Russian as foreign languages in Hungary and Eastern Germany. Issue 2 (2nd April 2016) - Bruen, Jennifer; Sheridan, Vera
ABSTRACT: This paper considers the impact of geopolitical factors, and in particular the collapse of Communism and EU accession, on language education policy and practice in Central and Eastern Europe (CEE). CEE is understood here as referring to the former soviet-controlled, eastern bloc counties of Bulgaria, the Czech Republic, East Germany, Hungary, Poland, Romania and Slovakia. A particular focus is placed in this paper on the teaching of English and Russian as foreign languages in Hungary and the former German Democratic Republic (GDR). The paper begins by reviewing current thinking in the field of language education policy and practice. It then provides an overview of developments in language education policy and practice in CEE more generally before focussing on two case-studies of language education policy and practice in Hungary and the former GDR. Implications both for language education policy and practice in CEE and for the nature of research in this field are discussed.